Pembuatan video Promosi di Perpustakaan SMP N 18 Padang - Azim, M Aulia; Ardoni, Ardoni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2019)
AbstractThe writing of this paper aims to discuss the stages of making a promotional video in the Library at SMPN 18 Padang. This study aims to describe the stages of making videos as a means of promoting the library SMPN 18 Padang. This type of research is qualitative with descriptive methods. Data was collected through observation and interviews with the Head of the Library and Librarian SMPN 18 Padang. And with the help of reading material related to video and library promotion. Based on analyzing the data it can be concluded that the steps in making a library promotion video are as follows: First, pre-production is the initial stage before the video production consists of idea discovery, synopsis, treatment, storyboarding, shotting script, production planning and production preparation. Second, production to realize all the steps in the pre-production stage. Third, post-production is the final stage in video production before the video is ready to be presented.Keywords: observation, making a library promotion video, interview